Revocalising human geography: Decolonial language geographies beyond the nation-state. (February 2023) - Chapman, Eleanor
This paper emphasises the decolonial importance of geographical engagement with the materiality of language as an embodied and embedded relation. It shows how abstractions of language(s) as discrete, codified and possessable objects participate in a 'coloniality of language' that risks obscuring alternative geographies of language within, against and beyond the territorialised monolingualism of the colonial nation-state. Through considering Italian philosopher Adriana Cavarero's analysis of Western modernity's systematic 'devocalisation of logos' from a modernity/coloniality perspective, I argue that geographical consideration of language as a 'revocalised' relation could contribute to moving beyond colonial and (ethno)nationalist geographies of language.